2016
DOI: 10.1075/wll.19.2.01fes
|View full text |Cite
|
Sign up to set email alerts
|

Strategy training and mind-mapping facilitates children’s hypertext comprehension

Abstract: Children in primary school read hypertext for comprehension. However, children typically are taught reading strategies for linear text, while these strategies are not automatically transferrable one-to-one to hypertext. In the present study, a training group of 55 sixth-graders were taught four hypertext reading strategies (planning, monitoring, evaluation and elaboration) via mind mapping and the usage of a prompting paper-card. A control group of 29 children received no strategy training. We examined to what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Unexpectedly, EMMEs combined with contrasting cases have a rather modest impact in improving students' navigation, as captured by our navigation indices. Concurring with prior research (Fesel et al, 2016;Kuo & Hwang, 2014), our instructional program produced an increase in reading times of the main document during the question-answering task. However, this effect is not selectively manifested in increased times for relevant pages or in decreased times for irrelevant pages.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Unexpectedly, EMMEs combined with contrasting cases have a rather modest impact in improving students' navigation, as captured by our navigation indices. Concurring with prior research (Fesel et al, 2016;Kuo & Hwang, 2014), our instructional program produced an increase in reading times of the main document during the question-answering task. However, this effect is not selectively manifested in increased times for relevant pages or in decreased times for irrelevant pages.…”
Section: Discussionmentioning
confidence: 52%
“…Four main instructional methods have been used in the literature, including direct instruction (Kuiper, Volman & Terwell, 2008Kuo & Hwang, 2014), different types of scaffolds (Argelago´s & Pifarre´, 2012;De Vries, van der Meij & Lazonder, 2008;Fesel, Segers, De Leeuw, & Verhoeven, 2016;Walraven, Brand-Gruwel, & Boshuizen, 2010), work in pairs (De Vries et al, 2008;Fesel et al, Kuiper et al (2008) 5th grade Direct instruction, work in pairs…”
Section: Instruction Of Digital Reading Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially students with lower vocabulary levels need additional help. Students may benefit from explicit training on how to read hypertexts, and on what they should pay attention to while navigating the networked hypertext (see e.g., Fesel, Segers, de Leeuw, & Verhoeven, ). In conclusion, we showed that for 13‐year olds, reading a networked hypertext negatively impacts comprehension and navigation behaviour, especially for those with lower vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) , the efficacy of constructing maps for integrated understanding has been only tested with Secondary school and older students, although previous studies suggest that students as young as 6th graders can be instructed to integrate information from texts ( Martínez et al., 2015 ; Wissinger & De La Paz, 2016 ). In addition, recent research has shown that concept maps can be effectively use with 6th graders to teach other advance literacy strategies, such as navigating hypertexts ( Fesel et al., 2016 ). The meta-analysis conducted by Schroeder et al.…”
Section: Introductionmentioning
confidence: 99%